2017
DOI: 10.1111/vde.12433
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a terbinafine–florfenicol–betamethasone acetate otic gel on the quality of life of dogs with acute otitis externa and their owners

Abstract: Background -Treatment of canine otitis externa with owner-administered products can be difficult.Objectives -To evaluate otic treatment administered by a veterinarian on quality of life (QoL) of dogs with otitis externa and their owners, and on clinical and cytology parameters of otitis; compared to an owner-administered treatment.Animals -Fifty client-owned dogs randomly randomized into two groups and treated for 2 weeks.Methods -Veterinarians treated Group A dogs with a veterinary licensed otic gel on two oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 17 publications
0
27
1
3
Order By: Relevance
“…One study by Noli [17] considered the benefits in terms of clinical efficacy, owner compliance and quality of life for owner and pet of a long-acting gel containing an antibioticantimycotic-glucocorticoid combination, administered by the veterinary surgeon once weekly. Conclusions from the work suggested that when a veterinarian administered an otic gel it provided equivalent efficacy but a higher quality of life to dogs with otitis externa and their owners, compared to an owner administering a topical otic therapy [17]. Based on the above-noted study, it would appear that owners favour products, in this case an antibiotic, that do not have to be used at home and prefer medication that is administered on a less frequent basis by their veterinarian.…”
Section: Introductionmentioning
confidence: 99%
“…One study by Noli [17] considered the benefits in terms of clinical efficacy, owner compliance and quality of life for owner and pet of a long-acting gel containing an antibioticantimycotic-glucocorticoid combination, administered by the veterinary surgeon once weekly. Conclusions from the work suggested that when a veterinarian administered an otic gel it provided equivalent efficacy but a higher quality of life to dogs with otitis externa and their owners, compared to an owner administering a topical otic therapy [17]. Based on the above-noted study, it would appear that owners favour products, in this case an antibiotic, that do not have to be used at home and prefer medication that is administered on a less frequent basis by their veterinarian.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, commensal microbes from the external ear canal of normal dogs can proliferate—often because of the underlying factors listed above—and infections with pathogens such as Staphylococcus pseudintermedius, Pseudomonas aeruginosa, Proteus mirabilis and Malassezia pachydermatis appear to be the dominant problem [4, 5]. The impact of OE is notable, as otitis diminishes the quality of life of dogs and their owners [6]. …”
Section: Introductionmentioning
confidence: 99%
“…The need for once or twice daily drug application into painful and/or stenotic ear canals can be stressful for owners and lead to aggressive behaviours from dogs [6]. Furthermore, in multidose presentations the repeated placement of the tip of the product into infected ear canals could potentially lead to their mutual microbial cross-contamination similar to may be seen with otoscope tips [4].…”
Section: Introductionmentioning
confidence: 99%
“…Die Reduktion der Zellzahlen für Kokken, Stäbchen und Neutrophile war bei Einsatz des Gels und des Kontrollpräparats vergleichbar, sodass die zytologisch verifizierbare Verbesserung in beiden Gruppen als vergleichbar gelten kann. Die aktuelle Studie berichtet von vergleichbaren zytologischen Ergebnissen eines zweimal im wöchentlichen Abstand anzuwendenden Ohrengels mit einem kommerziellen täglich zu applizierenden Otologikum (41). In dieser Studie war allerdings Table 4 Results of bacteriological culture at baseline and after 10 days of treatment with a gel preparation enriched with marbofloxacin, dexamethasone and enilconazole (group A) or a combination product containing marbofloxacin/ dexamethasone/clotrimazole (group B).…”
Section: Kokkenunclassified
“…Im Vergleich dazu konnte für ein neu zugelassenes, nur einmal wöchentlich zu applizierendes Ohrengel mit den Inhaltstoffen Florfenicol, Terbinafin und Betamethasonacetat (Osurnia®, Elanco Animal Health) eine klinische Remission nach 45 Tagen in knapp 64 % der Fälle gezeigt werden (3). Eine aktuelle Studie zu diesem Ohrengel zeigt im Vergleich zu einem täglich vom Besitzer zu applizierenden Otologikum eine adäquate Reduktion der klinischen Symptome und Verbesserung der Lebensqualität bei standardisierten Kriterien(41). Diagnostik und Therapie der Grunderkrankung sind meist nach 10 Tagen noch nicht abgeschlossen.…”
unclassified